Análise de compatibilidade entre risco e contaminação das águas superficiais e subterrâneas na bacia do rio Jacarecica – Maceió/AL - Vieira, Jeilson Lima (2014)
Changing the environment in which they inhabit all living beings is provided through large interference. These modifications are more widespread antropicamente, explaining that the man is more agent transformer that inhabits the Earth. These transformations are accentuated because of activities that have great power of contamination, particularly when they generate waste and they are released into water bodies without proper treatment. These releases when made available in urban watersheds generate significant pressures, leading to great risks to water resources and consequently to the population. The risk analysis applied to watersheds allows the orientation and adaptation of potentially polluting activities, through the establishment of conditions, aimed at improving the quality of the water. However, a question is raised: one can assume that the quality of the water of the springs reflects the results indicated in the risk analysis of the watershed? Leaving this questioning, this work aimed to study the compatibility between risk analysis and contamination of waters in the catchment area of the river Jacarecica, located in the urban area of the city of Maceió and that is water drop through transposition of bowls. To this end, we used the qualitative method of risk analysis and in parallel were collected samples of surface water and groundwater in field campaigns, being subsequently analyzed twenty-one parameters related to water quality. The field data were also compared to the parameters released by potentially polluting activities. The results obtained, it was found that there is compatibility between the risk obtained and water quality in some of these parameters. In addition, the analysis showed that were exceeded limits of quality established by the brazilian legislation in some parameters.